PENGARUH MEDIA PENDINGIN DALAM PROSES TEMPER QUENCH TERHADAP KEKUATAN IMPAK DAN KEKERASAN AISI 1045 - Weriono Weriono (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2019)
Steel materials is widely used as a component of the gears, shafts and bearing that required several factors such as impact strength, , hardness , toughness, ductility and. Etc. The process tempering includes heating steel AISI 1045 at low temperatures 2000C and 3000C, maintained at a particular time and refrigerated, oil cooling oil, water and oil plus water (mix). The purpose of this research is to acknowledge the changing impact strength and hardness material resulting from the process of tempering so getting to specifications and standards impact strength. hardness of materials. Impact strength highest cooling oil d = 19 mm temperature 2000C =14,43x104 joule / m2 and d = 19 mm temperature 3000C = 14,62x104 joule /m2 and cooling oil plus water (mix) d=2mm 2000C 11,23x104 joule / m2 and d = 25 mm temperature 3000C 12,96x104 joule / m2. In a cooling oil hardness highest d = 25 mm 3000C from the edge (Ra) 37,5 HRC and lowest d = 19 mm 2000C temperature from the edge (Ra) 18,5 HRC, water cooling hardness highest d = 25mm 3000C from the edge (Ra) 43 HRC and lowest temperature d=19 mm 2000C from the edge (Ra) 23 HRC and cooling plus water(mix) the highest hardnesst (Ra) d=19mm 2000C from the edge (Ra) 36,5 HRC and lowest d=25mm 3000c temperature from the edge (Ra) 16 HRC.Impact strength by the cooling oil has value greater strength from cooling water and cooling oil plus water. The hardness of materials by the highest water cooler temperatures d=25 mm 300 0c from the edge 43HRC than media cooling oil and oil plus water. The impact strength highest with cooling oil and hardness highest with cooling water then the impact strength and hardness materials non uniform in any variation diameter.